Предмет: Алгебра,
автор: Марина575888
Решите квадратное уравнение
(х+6) (х-7)=-х+7
(4-х)(4+х)=х²-2
Ответы
Автор ответа:
0
1) ( x + 6)(x - 7) = - x + 7
x² - x - 42 = - x + 7
x² - x + x = 7 + 42
x² = 49
x1 = 7
x2 = - 7
Ответ: x1 = 7, x2 = - 7.
x² - x - 42 = - x + 7
x² - x + x = 7 + 42
x² = 49
x1 = 7
x2 = - 7
Ответ: x1 = 7, x2 = - 7.
Похожие вопросы
Предмет: Математика,
автор: elenaguseva4206
Предмет: Алгебра,
автор: kapxud
Предмет: Математика,
автор: zenfiraqurbanaliyeva
Предмет: Математика,
автор: gorbunovsp
Предмет: Биология,
автор: Аноним